Strategi Pokmaswas Dalam Pengembangan Hutan Mangrove di Desa Pelambung - Metha Warissa; Dini Indriani Aulia Putri; Muhammad Rizky Febriansyah Lubis; Siti Arieta (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes the strategy of the Community Monitoring Group (Pokmaswas) in developing mangrove forests in Pelambung Village, Tanjung Balai Karimun, Riau Islands. This study aims to explore Pokmaswas management patterns and their impacts on local communities and coastal ecosystems. Mangrove forests play a crucial role in maintaining ecosystem balance, protecting coasts from abrasion, flooding, and storms, and supporting the biodiversity of fish, shrimp, and crabs. In Indonesia, mangrove area has decreased drastically from 5.2 million hectares in 1982 to around 2.5 million hectares due to land conversion, logging, and pollution. In Pelambung Village, Pokmaswas, established in 2023, began rehabilitation by planting 5,000 mangrove seedlings such as Rhizophora (mangrove), Avicennia (api-api), and Sonneratia. This qualitative, descriptive study, using observation, local community interviews, and documentation techniques, was conducted from July to August 2024. The Community Development Group (Pokmaswas) is active in nursery, harvesting, maintenance, monitoring, and ecotourism development, generating economic benefits (job creation, mangrove coffee MSMEs and miniature canoes), ecological benefits (protection from abrasion, increased fisherman's catch), and biological benefits (marine biota habitat). Challenges include limited funding, pest attacks, and integration with regional development.